THU0307 Validation of JADAS in international league against rheumatism (ILAR) subtypes of juvenile idiopathic arthritis (JIA). (23rd January 2014) - Mcerlane, F.; Beresford, M.W.; Baildam, E.M.; Chieng, S.E.; Davidson, J.; Foster, H.E.; Gardner-Medwin, J.; Lunt, M.; Wedderburn, L.R.; Hyrich, K.L.; Thomson, W.
Abstract : Background: Juvenile Arthritis Disease Activity Score (JADAS) is a 4 variable disease activity (DA) score for JIA (including active 10, 27 or 71 joint count (AJC), physician global assessment (PGA), parent/child global evaluation (PGE) and ESR). Much of the original validation data were derived from clinical trials (predominance of polyarticular course disease). The validity of JADAS for all ILAR subtypes of JIA in the routine clinical setting is unknown. Objectives: To investigate the construct validity of JADAS in all ILAR JIA subtypes in a prospective inception cohort of UK children with new onset inflammatory arthritis at the time of initial presentation. Methods: JADAS 10, 27 and 71 were determined for all children in the Childhood Arthritis Prospective Study (CAPS) with complete data available at baseline. Correlation of JADAS 10, 27 and 71 with single DA markers was determined for all ILAR subtypes of JIA (Spearman's rank statistic). Results: 354/1041 (34%) children had all 4 variables available at baseline. 994/1041 (95%) had AJC available, 811 (78%) PGA, 694 (67%) PGE and 647 (62%) ESR. Median age at disease onset was 6.8 years (IQR 2.8-10.8), median disease duration at diagnosis was 5.2 mths (IQR 2.5-10.9) and 64% were female. Correlation for the whole cohort between JADAS 71 and both JADAS 27 and 10 was 0.99, approaching 1 for all ILAR subtypes. There was a significant difference in median JADAS scores between subtypes (p<0.01) with the lowest in oligo-articular JIA and highest in systemic and polyarticular JIA. Correlation of JADAS71 with single markers of DA ranged from 0.48-0.75 for the whole cohort (see Table 1 ). Within the individual subtypes, the strongest correlation was with AJC (range 0.71-0.94). Correlation with PGA and PGE was moderate (range 0.29-0.75) and correlation with the ESR was strongest for undifferentiated and systemic JIA (0.76 and 0.59) but low to moderate for all other subtypes of JIA (range 0.2-0.41). Conclusions: JADAS71 correlated well with AJC, PGE and PGA but did not correlate well with the ESR in all ILAR subtypes. Correlation of JADAS71 with measures of disease severity is moderate, with some variation between subtypes. The ESR is not routinely measured in all children with JIA in the UK, as illustrated by its availability in just 62% of this cohort at baseline. Given the high frequency of unmeasured ESR assessments, we suggest further work is required to assess the validity of JADAS without inclusion of the ESR. Disclosure of Interest: None Declared